(untitled) (Research, Society and Development, 2024)
Objective: To discuss social scientists dedicated to health and their contributions to medicine and dentistry. Methodology: online searches using data published in VHL/BIREME, PUBMED Central, Science Direct, Web of Science, Research, Society and Development Journal and Google Academy. Results: We used 46 articles to compose this work. Conclusion: We obtained a literature review that addresses what a social scientist is applied to health and what its impact is on dentistry. A timeline was drawn, bringing some of the first social scientists, then we approached some more current ones bringing their contributions to health in general, finishing the article by creating an interface showing how these general contributions impacted dentistry.